DeImplementing Ineffective and Low-Value Clinical Practices: Research and Practice Opportunities in Community Oncology Settings. Issue 2 (24th February 2021) - Norton, Wynne E; McCaskill-Stevens, Worta; Chambers, David A; Stella, Philip J; Brawley, Otis W; Kramer, Barnett S
Abstract: Patients, practitioners, and policy makers are increasingly concerned about the delivery of ineffective or low-value clinical practices in cancer care settings. Research is needed on how to effectively deimplement these types of practices from cancer care. In this commentary, we spotlight the National Cancer Institute Community Oncology Research Program (NCORP), a national network of community oncology practices, and elaborate on how it is an ideal infrastructure for conducting rigorous, real-world research on deimplementation. We describe key multilevel issues that affect deimplementation and also serve as a guidepost for developing strategies to drive deimplementation. We describe optimal study designs for testing deimplementation strategies and elaborate on how and why the NCORP network is uniquely positioned to conduct rigorous and impactful deimplementation trials. The number and diversity of affiliated community oncology care sites, coupled with the overall objective of improving cancer care delivery, make the NCORP an opportune infrastructure for advancing deimplementation research while simultaneously improving the care of millions of cancer patients nationwide.